Carbon and nitrogen gain during the growth of orchid seedlings in nature. Issue 2 (21st January 2014) - Stöckel, Marcus; Těšitelová, Tamara; Jersáková, Jana; Bidartondo, Martin I.; Gebauer, Gerhard
Summary For germination and establishment, orchids depend on carbon (C) and nutrients supplied by mycorrhizal fungi. As adults, the majority of orchids then appear to become autotrophic. To compare the proportional C and nitrogen (N) gain from fungi in mycoheterotrophic seedlings and in adults, here we examined in the field C and N stable isotope compositions in seedlings and adults of orchids associated with ectomycorrhizal and saprotrophic fungi. Using a new highly sensitive approach, we measured the isotope compositions of seedlings and adults of four orchid species belonging to different functional groups: fully and partially mycoheterotrophic orchids associated with narrow or broad sets of ectomycorrhizal fungi, and two adult putatively autotrophic orchids associated exclusively with saprotrophic fungi. Seedlings of orchids associated with ectomycorrhizal fungi were enriched in 13C and 15N similarly to fully mycoheterotrophic adults. Seedlings of saprotroph‐associated orchids were also enriched in 13C and 15N, but unexpectedly their enrichment was significantly lower, making them hardly distinguishable from their respective adult stages and neighbouring autotrophic plants. We conclude that partial mycoheterotrophy among saprotroph‐associated orchids cannot be identified unequivocally based on C and N isotope compositions alone. Thus, partial mycoheterotrophy may be much more widely distributed among orchids than hitherto assumed.